Two neutrophilic dermatoses captured simultaneously on histology - Christina Wlodek; Nidhi Bhatt; Cameron Kennedy (Mattioli1885, 2016)
A number of neutrophilic dermatoses are associated with malignancies and their treatment. These rarely occur together in the same patient. A Caucasian 72-year-old male was treated for acute myeloid leukemia (AML) with chemotherapy including daunorubicin and cytarabine. Within 48 hours of commencing treatment, he developed pyrexia and, two days later, disseminated non-tender pink plaques on the limbs and trunk. A skin biopsy showed a dermal interstitial infiltrate of lymphocytes, histiocytoid cells and predominantly neutrophils. This extended into the subcutis, where a neutrophilic lobular panniculitis was seen. These findings are consistent with Sweet's syndrome. In addition, a neutrophilic and lymphocytic infiltrate was also present around eccrine coils and lower ducts. The eccrine epithelium showed squamous metaplasia with dyskeratosis and sloughing into the lumen. These latter findings are consistent with neutrophilic eccrine hidradenitis (NEH). These two histologically distinct entities form part of the neutrophilic dermatoses that have been described in oncology patients with reports of concurrent or sequential occurrence of various neutrophilic dermatoses in the same patient. Ours, however, is only the second reported case of simultaneously captured Sweet's and NEH in the setting of AML. The most likely explanation is that of an epiphenomenon, whereby the neutrophilic infiltrate extended around the sweat glands in the context of the neutrophilic dermatosis.